VILLAGE UNIT COOPERATIVE " TANI BAKTI " SEWON - Soetrisno Soetrisno Ph (Agro Ekonomi, 1978)
Background InformationVillage Unit Cooperative (VUC) "Tani Bhakti" lies in Subdistrict "Sewon", "Bantul" Regensy, Yogyakarta Special Region. It lies in the South of Yogyakarta Municepolity, around 7 kilometers (4.5 miles) from the town. The area of VUC "Tani Bhakti" covering 4 villages, over than 18000 hectares irrigated land. The biggest part of its population working on agriculture consisted both of land owning farmers and farmer-workers The rest working on small trading, handicraft,. housing construction, becak drivers, smallenterprises, governmental services, etc.Lurah is the head of local government. He is helped by several pamongs or officials. Each village consisting of around 15 sub villages all of those are headed by Kepala Dukuh. The average land owned by each farmer is less than a quarter hectare (around.15 hectares) most arable lands are fertile. They are volcanu and irrigated land_ 'I he total population is about 53.000 or about 12.000 families. Density of population is around 1600 per square kilometer